Pengaruh Gaya Kepemimpinan Dan Budaya Organisasi Terhadap Kinerja Karyawan Pada Kantor Kecamatan Panggungrejo Kabupaten Blitar - Pratikto, Agung (Otonomi, 2020)
The purpose of this study is to analyze whether the variables of leadership style and organizational culture affect the performance of employees at the Panggungrejo District Office in Blitar Regency simultaneously or partially, as well as analyzing the most dominant variables among the leadership styles and organizational culture. The population in this study were all employees in the District Office of Panggungrejo, Blitar Regency, amounting to 31 (thirty one) people. In this study, because the population is relatively small and relatively easy to reach, the authors use the total sampling method by using all employees in the population. The analytical method used in this research is multiple linear regression analysis. The results showed that the leadership style and organizational culture together had an influence on the performance of employees at the Panggungrejo District Office in Blitar Regency. Leadership style does not have an influence on employee performance at the Panggungrejo District Office in Blitar Regency. Organizational culture has no influence on employee performance at the Panggungrejo District Office in Blitar Regency. Organizational culture is the most dominant variable in this study.